2013
DOI: 10.1111/cge.12253
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis for patients with IL‐12 receptor β1 deficiency

Abstract: Autosomal recessive interleukin-12 receptor β1 (IL-12Rβ1) deficiency has been described as the most common cause of Mendelian susceptibility to mycobacterial disease (MSMD), characterized by clinical disease due to weakly virulent mycobacteria such as Bacille Calmette-Guérin (BCG) vaccines and environmental mycobacteria (EM) in children who are normally resistant to most infectious agents. Here, we report the cases of five patients with mycobacterial infection, including one with systemic lupus erythematosus (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…Worth of note, PHA-blasts from Case 2 produced >4,000 pg/mL of IFN-γ, which is close to the levels observed in the controls (Figure 4A), and contrasting to the situation in the younger affected brother (Case 3). There are reports of close to normal and even higher levels of IFN-γ production in PHA- or BCG-blasts of a few other patients with IMD30 (de Jong et al, 1998; Caragol et al, 2003; Lichtenauer-Kaligis et al, 2003; Moraes-Vasconcelos et al, 2005; Schepers et al, 2013; Ramirez-Alejo et al, 2014). …”
Section: Kindred Cmentioning
confidence: 97%
“…Worth of note, PHA-blasts from Case 2 produced >4,000 pg/mL of IFN-γ, which is close to the levels observed in the controls (Figure 4A), and contrasting to the situation in the younger affected brother (Case 3). There are reports of close to normal and even higher levels of IFN-γ production in PHA- or BCG-blasts of a few other patients with IMD30 (de Jong et al, 1998; Caragol et al, 2003; Lichtenauer-Kaligis et al, 2003; Moraes-Vasconcelos et al, 2005; Schepers et al, 2013; Ramirez-Alejo et al, 2014). …”
Section: Kindred Cmentioning
confidence: 97%
“…Functional IL-12 receptors are expressed primarily on activated T and NK cells. In total, 180 patients from 136 kindreds have been described [2, 21, 25, 28, 30, 31, 3436, 3840, 43, 44, 86, 102, 188233]. The list of known IL12RB1 mutations is increasing, with 78 identified to date, including nonsense ( n =18), missense ( n =24), and splice-site mutations ( n =13), small deletions ( n =16), large deletions ( n =3) insertions ( n =1), and duplications ( n =3) (www.LOVD.nl/IL12RB1) [191] (Figure 1).…”
Section: Complete Il-12rβ1 Deficiencymentioning
confidence: 99%
“…Indeed, 47 of the 179 patients died (26%), 8 are asymptomatic (the oldest being 22 years old in 2010) and 124 were alive at the time of their description, the oldest of these patients being 51 years old in 2010 [28, 198]. Mycobacterial infections are the most frequent infections observed in these patients (BCG, M. avium , M. avium intracellulare complex, M. chelonae , M. fortuitum , M. fortuitum - chelonae complex, M. genevense , M. gordonae , M. tilburgii , M. triplex , M. simiae ) [28, 34, 36, 86, 116, 190, 193, 194, 198, 199, 204, 206, 208210, 214, 215, 235, 236]. Remarkably, BCG vaccination or disease protects against subsequent EM disease [28, 194] (Figure 5).…”
Section: Complete Il-12rβ1 Deficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Such defects often lead to absent or reduced IFNg production and deficient macrophage activation. 6 The diagnosis of an IL-12 receptor defect is supported by functional studies and confirmed by genetic testing. During functional studies, blood samples from the individual are exposed to IL-12 and to mycobacterial antigens, and levels of IFNg produced are measured.…”
Section: Discussionmentioning
confidence: 98%